Installing The Maximum Renewable Energy And Studying Its Effect On Tulkarm City - Samha, Taqwa; Aqra, Lamees (My University, 2021)
The Palestinian Territories relies on Israel for 100% of its fossil fuels imports and for 87% of its electricity imports. Since the main energy source is solar, wind and Biomass we thought about using an available renewable energy which will decrease the energy reliance on other countries with improving the Palestinian population’s access to energy. Although, the connection to power distribution networks of the growing number and capacity of renewable energy sources installations implies overcoming several technical challenges of distribution network operators. The purpose of this project is to study the effect of photovoltaic cells on Tulkarm network by assessing the upper limit of the size of the PV systems that can be connected to the medium pressure network, by using Etap software while Adding the solar cells to loads and connection points and compare of them. By using the PV systems, we will decrease network loads in this city since Tulkarm is suffering from continuous interruption of the electricity duo to excess consumption, constant pressure on the network also there will be no negative effects and will be our best environmental friend.